1994
DOI: 10.1111/j.1476-5381.1994.tb14020.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by insulin treatment of endothelial dysfunction but not enhanced noradrenaline‐induced contractility in mesenteric resistance arteries from streptozotocin‐induced diabetic rats

Abstract: 1 Streptozotocin-induced diabetic rats (Wistar) were implanted with sustained release insulin pellets (release rate =4 u day-') or with placebo pellets (palmitic acid) from the onset of glycosuria. 2 Noradrenaline sensitivity, endothelium-dependent relaxation to acetylcholine and endotheliumindependent relaxation to sodium nitroprusside were assessed in mesenteric resistance arteries from the insulin-treated (IT) diabetic animals and compared to placebo-implanted (PI) diabetics and age-matched controls. 3 Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
2
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 60 publications
(61 reference statements)
8
53
2
1
Order By: Relevance
“…The vascular endothelial dysfunction developed in streptozotocin-induced diabetic rats can be recovered after 8 to 12 weeks of treatment with insulin [51], or with a pancreatic islet transplantation [52]. In these studies, the improvement of endothelial function was accompanied by a parallel improvement in metabolic control, estimated by HbA 1c values [52] or by the extinction of glycosuria or ketonuria [51].…”
Section: Discussionmentioning
confidence: 63%
“…The vascular endothelial dysfunction developed in streptozotocin-induced diabetic rats can be recovered after 8 to 12 weeks of treatment with insulin [51], or with a pancreatic islet transplantation [52]. In these studies, the improvement of endothelial function was accompanied by a parallel improvement in metabolic control, estimated by HbA 1c values [52] or by the extinction of glycosuria or ketonuria [51].…”
Section: Discussionmentioning
confidence: 63%
“…By contrast, the majority of studies of both large isolated arteries and resistance from rats with chemically-induced diabetes have shown an enhanced senstivity to contractile agents (Harris & MacLeod, 1988;Legan, 1989;Owen & Carrier, 1980;MacLeod & McNeill, 1985;Friedman, 1989;Taylor et al, 1992). Moreover, a study of insulin-treated STZ-induced diabetic rats, showed that insulin did not prevent enhanced contractility to NA, although it did prevent impaired endothelium-dependent relaxation to ACh (Taylor et al, 1994a). These findings contrast with those from human studies, which have shown resistance arteries from insulin dependent diabetis mellitus (IDDM) patients without complications other than background retinopathy, display impaired contractile responses to NA, and impaired endothelium-dependent relaxation to ACh (McNally et al, 1994); furthermore, resistance arteries from healthy volunteers exposed to increasing concentrations of insulin show decreased contractile response to NA in a dose-dependent manner (McNally et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia Impaired ACh-induced relaxation was reversed by chronic insulin treatment (Wang et al, 1993;Taylor et al, 1994a), but not by acute insulin administration, even though glycaemia was normalized (Wang et al, 1993;Bucala et al, 1991). Defective endothelium-dependent relaxation was restored 4 weeks after pancreatic transplantation, performed in rats after 12 weeks of diabetes (Pieper et al, 1998a).…”
Section: Aetiology Of Endothelial Dysfunction In Diabetesmentioning
confidence: 99%